Shorebirds exhibit niche partitioning on multiple dimensions at a small staging site on the Northumberland Strait, New Brunswick, Canada - Sara C. Bellefontaine; Diana J. Hamilton (Canadian Science Publishing, 2023)
Animal populations take advantage of environmental heterogeneity to partition themselves into microhabitat niches. Such partitioning plays an important role in regulating interspecific competition and community structure by allowing multiple species to coexist. Atlantic Canada has many small coastal staging sites that host southbound migrant shorebirds. However, most shorebird studies in the region have been focused on larger sites in the Bay of Fundy, resulting in limited knowledge about staging ecology at these small sites, which often host more diverse shorebird assemblages. We examined niche partitioning by shorebirds on the Northumberland Strait, New Brunswick, Canada, to better understand how small coastal staging sites support diverse shorebird populations. We found evidence of partitioning on three niche dimensions: space, foraging behaviour, and diet. Most species specialized in at least one dimension, with foraging constraints based on bill morphology and habitat access based on species size likely driving segregation. Environmental heterogeneity at sites on the Northumberland Strait created multiple dimensions for segregation and fulfilled the niche requirements of diverse shorebird species during migratory staging. These findings broaden our understanding of staging ecology of multispecies flocks and suggest that conservation of small coastal sites is important for success of migratory shorebirds in Atlantic Canada.